The traps of persuasion (An approach to the fable of the crow and the fox according to the versions of El Conde Lucanor and El Libro de Buen Amor) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
Fable is a type of didactic story in which the characters are generally personified animals and whose narrative events usually illustrate, in a way that is intended to be persuasive, a certain maxim or moral principle. Such a maxim or principle is usually made explicit at the end of the story through verses or sententious phrases that constitute a moral. For this reason, this type of story has a relatively simple structure: the characters lack, at least in appearance, psychological depth; Descriptions of space and environment are limited to only the notations that are just and necessary to place the action in a minimum space-time framework. Fables, to the extent that they explain their morals, are proposed as “closed stories” in the sense that the narrator (or character) himself provides a precise reading key. That is, the story tends to restrict as much as possible the plural meaning of the literary text, inciting a defined interpretation, aimed at producing an ethical-moral intervention in the reader.